2011
DOI: 10.1111/j.1751-7176.2011.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Are There Pleiotropic Effects of Antihypertensive Medications or Is It All About the Blood Pressure in the Patient With Diabetes and Hypertension?

Abstract: Many small studies with varied surrogate end points and numerous preclinical data have suggested the likelihood of there being specific benefits that exceed simple blood pressure control with drug classes such as angiotensin‐converting enzyme inhibitors, angiotensin receptor blockers, and calcium channel blockers, which may be particularly relevant to the patient with diabetes and hypertension. Large clinical trials, however, have provided only token support for this idea. Likewise, meta‐analyses that have inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Thus, RAS activity may be a key mechanistic contributor to functional decline in this population. Moreover, in addition to effects in mitigating hypertension, several antihypertensive drugs are also thought to have pleiotropic physiologic effects that extend beyond lowering blood pressure (Sica, 2011; Zoccali and Mallamaci, 2014). For instance, prior work has demonstrated the effects of angiotensin converting enzyme (ACE) inhibitors in endocrine signaling, regulation to tissue-specific oxidative stress and inflammation, and in the regulation of body composition (Carter et al, 2011; Giovannini et al, 2010; Marzetti et al, 2012).…”
Section: Collateral Health Risks Among Older Adults With Hypertensionmentioning
confidence: 99%
“…Thus, RAS activity may be a key mechanistic contributor to functional decline in this population. Moreover, in addition to effects in mitigating hypertension, several antihypertensive drugs are also thought to have pleiotropic physiologic effects that extend beyond lowering blood pressure (Sica, 2011; Zoccali and Mallamaci, 2014). For instance, prior work has demonstrated the effects of angiotensin converting enzyme (ACE) inhibitors in endocrine signaling, regulation to tissue-specific oxidative stress and inflammation, and in the regulation of body composition (Carter et al, 2011; Giovannini et al, 2010; Marzetti et al, 2012).…”
Section: Collateral Health Risks Among Older Adults With Hypertensionmentioning
confidence: 99%
“…As previously outlined (29, 30), the choice of first-line antihypertensive medications may have an important role on functional responses after exercise. For instance, ACE inhibitors have been suggested as a promising therapeutic option to target the rate of functional decline, potentially due to pleiotropic effects on body composition, angiogenesis, inflammation and oxidative stress (64,65). In fact, previous evidence has suggested that ACE inhibitors and exercise combined may attenuate declines in gait speed and on limitations of activities of daily-life (15,20,34).…”
Section: Discussionmentioning
confidence: 99%
“…20 However, these mild anti-inflammatory effects observed in a small number of patients may not have meaningful impact on stroke rates and CV outcomes if not accompanied by significant BP reduction. 21 One of the main reasons RAS antagonists may be less effective antihypertensive agents in African Americans is the different dose response compared with whites. 22 African Americans require higher doses of ACE inhibitors to achieve equivalent reductions in BP with whites.…”
Section: Discussionmentioning
confidence: 99%